2017
DOI: 10.7710/2162-3309.2169
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Attitudes toward Open Access and Scholarly Communications: Disciplinary Differences on an Urban and Health Science Campus

Abstract: Access to scholarship in the health sciences has greatly increased in the last decade. The adoption of the 2008 U.S. National Institutes of Health Public Access Policy and the launch of successful open access journals in health sciences have done much to move the exchange of scholarship beyond the subscription-only model. One might assume, therefore, that scholars publishing in the health sciences would be more supportive of these changes. However, the results of this survey of attitudes on a campus with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…When asked to identify the primary deposit method, 71% reported that repository staff deposit materials on behalf of their users. This was consistent with what was reported in the literature about low rates of author self-deposit (“self-archiving”) in IRs, especially in the health sciences [7]. Another 14% used “mediated self-deposit” as the primary method, meaning that authorized users could deposit materials, but repository staff reviewed, approved, and performed final posting for all materials.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When asked to identify the primary deposit method, 71% reported that repository staff deposit materials on behalf of their users. This was consistent with what was reported in the literature about low rates of author self-deposit (“self-archiving”) in IRs, especially in the health sciences [7]. Another 14% used “mediated self-deposit” as the primary method, meaning that authorized users could deposit materials, but repository staff reviewed, approved, and performed final posting for all materials.…”
Section: Resultssupporting
confidence: 88%
“…Loan and Sheikh analyzed 254 health and medical repositories utilizing the information listed in OpenDOAR [6]. In addition, Odell et al shared findings from a survey that they conducted at their institution that demonstrated that medical faculty were not responsive to changes in scholarly communication, which impacted their self-archiving activities in the IR [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite widely held assumptions that researchers in the sciences generally, and the health sciences specifically, are more accepting of OA, one study indicated that health sciences faculty at one institution in fact supported the (non-OA) status quo in scholarly publishing. 9 Another study showed that OA authors' perceptions can differ from those of their colleagues, even in the same discipline. For example, the altruistic goals of "Free Access" and "Audience Accessibility" most frequently motivated biomedical authors at the University of North Carolina and Duke University.…”
Section: Literature Reviewmentioning
confidence: 99%
“…OA has indeed grown, with around 50% of the most recent literature being freely available to the public (Archambault, 2018; Archambault et al, 2014; Piwowar et al, 2018). Yet, OA remains low on the priority lists of faculty (Dallmeier-Tiessen et al, 2011; Gaines, 2015; Odell et al, 2017), even when surveys indicate that many faculty believe open access to their published works is beneficial to their careers due to wider readership (Dallmeier-Tiessen et al, 2011; Gaines, 2015; Odell et al, 2017). It seems these faculty simultaneously hold the conflicting belief that traditional publishing is better for their careers overall because it is valued more in the RPT process (Migheli and Ramello, 2014; Peekhaus and Proferes, 2015; Peekhaus and Proferes, 2016; Rodriguez, 2014).…”
Section: Introductionmentioning
confidence: 99%